Pengaruh Pelaksanaan CODE STEMI Terhadap Strategi Pemasaran RSUPN Dr Cipto Mangunkusumo - Ginanjar, Eka; Sjaaf, Amal Chalik; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
Nowadays, the competition in the hospital industry business is getting tougher. For this reason, hospitals are required to have innovations and strategies to attract patients. One of the necessary things to encourage patients to come to the hospital is a good hospital marketing strategy. This research aims to identify the impact of CODE STEMI program on the marketing strategy of the Cipto Mangunkusumo National General Hospital. This research uses quantitative methods by tracking medical records and administrative documents, as well as qualitative methods by observation and in-depth interviews. The results showed a decrease in mortality, MACE, door to balloon time, total cost, and length of stay after the implementation of the CODE STEMI program. These results have a good impact on the product marketing mix, such as price, distribution, people, processes, and physical facilities. Patients are satisfied with the services provided, and the number of STEMI patients coming to the hospital has increased since the implementation of the CODE STEMI program. Based on these results, it was concluded that the CODE STEMI program had a positive impact on the marketing strategy of RSUPN Dr. Cipto Mangunkusumo. Nowadays, the competition in the hospital industry business is getting tougher. For this reason, hospitals are required to have innovations and strategies to attract patients. One of the necessary things to encourage patients to come to the hospital is a good hospital marketing strategy. This research aims to identify the impact of CODE STEMI program on the marketing strategy of the Cipto Mangunkusumo National General Hospital. This research uses quantitative methods by tracking medical records and administrative documents, as well as qualitative methods by observation and in-depth interviews. The results showed a decrease in mortality, MACE, door to balloon time, total cost, and length of stay after the implementation of the CODE STEMI program. These results have a good impact on the product marketing mix, such as price, distribution, people, processes, and physical facilities. Patients are satisfied with the services provided, and the number of STEMI patients coming to the hospital has increased since the implementation of the CODE STEMI program. Based on these results, it was concluded that the CODE STEMI program had a positive impact on the marketing strategy of RSUPN Dr. Cipto Mangunkusumo.